Reading Contemporary Imaginaries inspired by the Middle Ages Narratives through Mass Media Images - Teresa Torres Eça; Rosângela Aparecida da Conceição (Anastasis: Research in Medieval Culture and Art)
In this article, the authors will approach images from film and games industry to discuss trends in contemporary young people and young adults’ subcultures. The images will serve as a basis to debate digital natives fascination by metanarratives grounded on stories inspired by Middle Ages stories. A set of images will be discussed through methodologies of visual analysis that may give some insights about the fascination transmitted by medieval stories to young people and young adults’ subcultures.